Simultaneous flue gas bioremediation and reduction of microalgal biomass production costs - Douskova, I; Doucha, J; Livansky, K; Machat, J; Novak, P; Umysova, D; Zachleder, V; Vitova, M (Applied microbiology and biotechnology, 2009)
A flue gas originating from a municipal waste incinerator was used as a source of CO(2) for the cultivation of the microalga Chlorella vulgaris, in order to decrease the biomass production costs and to bioremediate CO(2) simultaneously. The utilization of the flue gas containing 10-13% (v/v) CO(2) and 8-10% (v/v) O(2) for the photobioreactor agitation and CO(2) supply was proven to be convenient. The growth rate of algal cultures on the flue gas was even higher when compared with the control culture supplied by a mixture of pure CO(2) and air (11% (v/v) CO(2)). Correspondingly, the CO(2) fixation rate was also higher when using the flue gas (4.4 g CO(2) l(-1) 24 h(-1)) than using the control gas (3.0 g CO(2) l(-1) 24 h(-1)). The toxicological analysis of the biomass produced using untreated flue gas showed only a slight excess of mercury while all the other compounds (other heavy metals, polycyclic aromatic hydrocarbons, polychlorinated dibenzodioxins and dibenzofurans, and polychlorinated biphenyls) were below the limits required by the European Union foodstuff legislation. Fortunately, extending the flue gas treatment prior to the cultivation unit by a simple granulated activated carbon column led to an efficient absorption of gaseous mercury and to the algal biomass composition compliant with all the foodstuff legislation requirements.
Keywords: biotechnologie; Biodegradation, Environmental; Chlorella vulgaris; Bioreactors; Gases; biodegradace; Biotechnology; biomasa; plyny; Biomass; bioreaktory; oxid uhličitý; Carbon Dioxide